2015
DOI: 10.1155/2015/186249
|View full text |Cite|
|
Sign up to set email alerts
|

Size of the Optic Nerve Head and Its Relationship with the Thickness of the Macular Ganglion Cell Complex and Peripapillary Retinal Nerve Fiber Layer in Patients with Primary Open Angle Glaucoma

Abstract: Purpose. To evaluate the relationships among the optic nerve head (ONH) area, macular ganglion cell complex (mGCC) thickness, circumpapillary retinal nerve fiber layer (cpRNFL) thickness, and visual field defects in patients with primary open angle glaucoma (POAG). Methods. This retrospective study included 90 eyes of 90 patients with POAG. The ONH area, rim area, mGCC thickness, and cpRNFL thickness were measured using optical coherence tomography. Mean deviation (MD) was measured using standard automated per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Studies evaluating differences between patients with parafoveal and peripheral scotoma [2, 3, 1317, 26] found no differences in the optic disc area between the two groups. However, in our previous study [27], we found that the thicknesses of cpRNFL and mGCC were significantly positively correlated with the disc area in eyes with glaucoma. Smaller discs may have thinner cpRNFL and mGCC and be susceptible to the inferior VF defect.…”
Section: Discussionmentioning
confidence: 61%
“…Studies evaluating differences between patients with parafoveal and peripheral scotoma [2, 3, 1317, 26] found no differences in the optic disc area between the two groups. However, in our previous study [27], we found that the thicknesses of cpRNFL and mGCC were significantly positively correlated with the disc area in eyes with glaucoma. Smaller discs may have thinner cpRNFL and mGCC and be susceptible to the inferior VF defect.…”
Section: Discussionmentioning
confidence: 61%
“…Our data suggest that optical discs with larger area have greater MCD and MD. The relationship between disc area and susceptibility to glaucomatous damage remains to be clarified [19]. Some authors suggest that patients with large discs have a higher incidence of glaucoma [20] [21], while others have found no such relationship [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…Novel research suggests that peripapillary RNFL alterations are detected with OCT earlier than with conventional methods such as visual field testing. 60 Furthermore, the peripapillary RNFL can be compared with the macular RNFL thickness and ganglion cell layer thickness to potentially monitor disease progression. Using OCT RNFL thickness analysis, some authors have reported a reduced thickness of the peripapillary RNFL in children affected with NF1 who have optic nerve gliomas.…”
Section: Ophthalmic and Adenexal Manifestationsmentioning
confidence: 99%